2019
DOI: 10.1186/s13063-019-3262-2
|View full text |Cite
|
Sign up to set email alerts
|

The iBobbly Aboriginal and Torres Strait Islander app project: Study protocol for a randomised controlled trial

Abstract: Background Suicide amongst Australian Aboriginal and Torres Strait Islander communities occurs at twice the rate of the general population and, with significant barriers to treatment, help-seeking prior to a suicide attempt is low. This trial aims to test the effectiveness of an app (iBobbly) designed with Aboriginal and Torres Strait Islander people for reducing suicidal ideation. Methods/design This is a two-arm randomised controlled trial that will compare iBobbly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…This is an important finding given the documented mental health challenges experienced by First Peoples of Australia, New Zealand, and the United States on account of intergenerational trauma [22]. It demonstrates that scientific research is responding to the mental and emotional challenges faced by First Nations populations [53].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This is an important finding given the documented mental health challenges experienced by First Peoples of Australia, New Zealand, and the United States on account of intergenerational trauma [22]. It demonstrates that scientific research is responding to the mental and emotional challenges faced by First Nations populations [53].…”
Section: Discussionmentioning
confidence: 89%
“…Importantly, beyond social or entertainment value, mobile devices offer significant potential for access to health support in scenarios where individuals hold concerns about face-to-face interaction. For example, tablets may facilitate help-seeking behavior for young people who experience concerns about social interaction and moral judgement when accessing mental health support [26,37,38,53,54]. This systematic review identified significant First Nations expertise that conceivably augmented favorable user perspectives of the mHealth interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that psychosocial interventions can help reduce self-harm risk [53], but trials of culturally adapted interventions that specifically target self-harm in Aboriginal and Torres Strait Islander populations are sparse [54]. A trial of a self-help mobile phone application, designed with Aboriginal and Torres Strait Islander people, aimed at reducing suicide ideation is currently ongoing [55]. Given the high proportion of Indigenous people living in regional and remote areas, and the high incidence of youth suicide in such areas, a research agenda aimed at profiling the unique psychological, social and cultural needs of these communities in relation to suicide and self-harm is required.…”
Section: Discussionmentioning
confidence: 99%
“…dMH services are identified as “mental health, suicide prevention and alcohol and other drugs services delivered via a digital platform”, which include the “provision of information, digital counselling services, treatment services (including assessment, triage and referral services) and peer-to-peer support services” [ 10 ]. Some examples of dMH services for Indigenous people include interventions delivered via smartphone applications [ 48 ], therapist-supported digital interventions on tablet devices [ 49 ], online CBT programs [ 50 ] and gamified CBT interventions [ 51 ]. For the purposes of this review, we will include studies reporting on the design, development or evaluation of mental health interventions, which use a digital platform (e.g.…”
Section: Methodsmentioning
confidence: 99%